Electric Bipole Antenna Model Study of a Basin Scale Fault System. Issue 1 (1st December 2016) - Costall, Alexander Ross; Harris, Brett; Pethick, Andrew; Schaa, Ralf
Abstract : The generation of electric fields with electric bipole transmitters are applicable at a wide range physical scales and for many subsurface exploration endeavors. Increase in transmitter power for a wide range of waveforms combined with receiver sensitivity has led to deeper exploration with electromagnetic methods. We investigate the optimal design of grounded bipole EM system for generation of electromagnetic fields over a basin-scale fault in Perth, W.A. The technical objective is to recover detailed electrical conductivity distribution proximal to and within a large fault system to depths of as much as 1000m below the surface. The ultimate geological imperative for the exercise is reveal possible change in solute concentration or hydraulic across these large fault systems. For example, imaging of the difference composition of fault core zone would be a valuable outcome. We investigate various combinations of receiving and transmitting antenna geometries in preparation for a field campaign intended to resolve electrical parameters and structures of this large fault system.